Description of the First Case of Adenomyomatosis of the Gallbladder in an Infant - Yuri A. Zarate; Katherine A. Bosanko; Chaowapong Jarasvaraparn; Jaime Vengoechea; Elizabeth M. McDonough (Hindawi Limited, 2014)
We report here the case of the youngest patient with adenomyomatosis of the gallbladder in a female infant diagnosed at 4 months of age. This diagnosis was made based on characteristic ultrasonography findings in a patient that was undergoing routine surveillance for a suspected clinical diagnosis of Beckwith-Wiedemann syndrome. The patient remains asymptomatic and currently no surgical interventions have been needed. We review the pathophysiology and ultrasonographic findings of this rare condition and present a comparison with the only other four pediatric cases of adenomyomatosis of the gallbladder.